Hand grip strength and risk of incident venous thromboembolism: The Tromsø study - Oda G. R. Leknessund; Vania M. Morelli; Bjørn Heine Strand; John‐Bjarne Hansen; Sigrid K. Brækkan (Research and Practice in Thrombosis and Haemostasis, 2022)
Abstract Background Hand grip strength (HGS), a common proxy of whole‐body muscular strength, is associated with a wide range of adverse health outcomes and mortality. However, there are limited data on the association between HGS and risk of venous thromboembolism (VTE). Objectives We aimed to investigate the association between HGS and risk of incident VTE in a population‐based cohort. Methods Participants (n = 13,704) from the fourth to seventh surveys of the Tromsø study (Tromsø4–Tromsø7, enrollment: 1994–2016) were followed throughout 2020, and all incident VTEs were recorded. HGS of the nondominant hand was measured using a Martin Vigorimeter (Tromsø4–Tromsø6) and a Jamar Digital Dynamometer (Tromsø7). Hazard ratios (HRs) for VTE with 95% confidence intervals (CIs) according to weak HGS (less than 25th percentile) versus normal HGS (25th percentile or greater) were estimated using Cox regression models and adjusted for age, sex, body height, body mass index, physical activity, cardiovascular disease, and cancer. Results During a median of 6.5 years of follow‐up, 545 incident VTEs occurred. Participants with weak HGS had a 27% higher risk of VTE (HR, 1.27; 95% CI, 1.03–1.57) compared to those with normal HGS. Subgroup analyses revealed that the point estimates were higher for unprovoked VTE (HR, 1.35; 95% CI, 0.96–1.91) and deep vein thrombosis (DVT; HR, 1.52; 95% CI, 1.14–2.01). Similar results were found in analyses restricted to men, women, and elderly (aged greater than 75 years). Conclusion A weak HGS was associated with increased risk of VTE, and particularly unprovoked VTE and isolated DVT. Our findings suggest that weak muscle strength may be a risk factor for VTE.